The Relationship Between Social Support and Resilience in Qur’an Memorizing at Santri SMP ISR in Malang City - Shofi Nuraini Dwiputri, Fitri; Tri Harsono, Yudi (KnE Social Sciences, 2022)
This study aimed to determine the relationship between social support and resilience in Islamic students who memorize the Qur’an at Junior High School ISR Malang City. The sample consisted of 110 students who were in the process of memorizing the Qur’an. Data were collected using a questionnaire consisting of two scales, namely the social support scale and the resilience scale. The social support scale, called the Multidimensional Scale of Perceived Social Support (MSPSS), consisted of 12 items, and was developed by Zimet et al. and adapted by Eva & Bisri. The resilience scale, called the Adolescent Resilience Scale, consisted of 21 items, and was developed by Oshio et al. and adapted by the researchers. Data were analyzed using Pearson’s product-moment correlation, resulting in a correlation coefficient of 0.675 (p < 0.05) which fell into the high and unidirectional categories. The results of this study therefore indicated a relationship between social support and resilience in Islamic students who memorize the Qur’an at SMP ISR Malang. Keywords: social support, resilience, Santri, memorizing the Qur’an